4.3 μW 10 fA‐sensitivity dual‐mode current converter for implantable glucose monitoring. Issue 19 (2nd September 2015) - Tan, Xi; Chen, Xianliang; Zhang, Yiwu; Wang, Junyu; Min, Hao; Huang, Yue; Mason, Andrew J.
Abstract : A low‐power, high‐sensitive current converter for implantable electrochemical glucose sensor tags based on radio frequency identification is presented. The current converter can work in the incremental sigma delta (ΣΔ) converter mode or the dual‐slope converter mode. The two modes can be switched automatically according to the input current value for the target measuring range from 10 fA to 1 nA. The dual‐mode converter offers a 10 fA‐input current sensitivity, 100 dB dynamic range and consumes 4.26 μW of power from a 1.5 V supply.